Capillary electrophoresis, high‐performance liquid chromatography, and thin‐layer chromatography analyses of phenolic compounds from rapeseed plants and evaluation of their antioxidant activity. Issue 2 (26th November 2018) - Huang, Yang; Jansen, Olivia; Frédérich, Michel; Mouithys‐Mickalad, Ange; Nys, Gwenaël; Servais, Anne‐Catherine; Crommen, Jacques; Jiang, Zhengjin; Fillet, Marianne
Abstract: Rapeseed plants, known for oil production, are also known to contain phenolic compounds such as phenolic acids and flavonoids, with potential antioxidant and anticancer activities. The separation and identification of 11 phenolic acids in rapeseed extracts (including leaves, flowers, Chinese seeds, Belgian seeds, and cake) by capillary electrophoresis were investigated. The results were compared with those obtained with high‐performance liquid chromatography and thin‐layer chromatography and showed that the capillary electrophoresis technique offers several advantages for the identification of phenolic compounds in various rapeseed extracts. The antioxidant activity of rapeseed extracts and reference compounds was evaluated using four different approaches, namely, 2, 2′‐azinobis‐ (3‐ethylbenzohiazoline‐6‐sulfonic acid assay, free radical 2, 2‐diphenyl‐1‐picrylhydrazyl assay, electron paramagnetic resonance spectroscopy and the measurement of the total polyphenol content. The contents of total polyphenols in the tested extracts were ranging between 5.4 and 21.1% m/m and ranked as follows: Chinese seeds ˃ Belgian seeds ˃ Flowers ˃ Cake ˃ Leaves.